Strategy for Developing Rafting as A Special Interest Tourism at Belaban Resort - Listiani, Kiara Ayu; Rifanjani, Slamet; Muflihati; Kusuma, Helmy Adhi (Journal of Sylva Indonesiana, 2023)
Bukit Baka Bukit Raya National Park in Indonesia has vast natural tourism potential, and one of its highlights is white water rafting at Belaban Resort. This study aimed to devise a strategy for developing rafting tourism at the Belaban Tana Kaya Resort. The research began in November 2021 and involved distributing questionnaires to respondents chosen through accidental sampling and conducting a Focus Group Discussion with the rafting tour manager at Resort Balaban. The data was analyzed using SWOT analysis, which helped identify the resort's strengths, weaknesses, opportunities, and threats. The results showed that the rafting tour at the Belaban Resort had a promising future, as it was in the first quadrant of the SWOT analysis, which supports aggressive growth policies while still adhering to the guidelines for sustainable tourism development based on national parks. The study's findings could guide the resort's management in devising a plan for developing rafting tourism sustainably, enhancing the resort's attractiveness to tourists, and boosting the local economy